Phylogenetic relationships among several freshwater fishes (Family: Cyprinidae) in Malaysia inferred from partial sequencing of the Cytochrome b mitochondrial DNA (mtDNA) gene - Esa, Yuzine; Japning, Jeffrine Rovie Ryan; Abdul Rahim, Khairul Adha; Siraj, Siti Shapor; Daud, Siti Khalijah; Tan, Soon Guan; Stephen, Sungan (Universiti Putra Malaysia Press, 2012)
The phylogenetic relationships among 23 species of Malaysian freshwater fishes in the family Cyprinidae was inferred by partial sequencing of the Cytochrome b (Cyt b) mitochondrial gene. Samples were collected from various localities in Sarawak, Sabah and Peninsular Malaysia. The inferred phylogeny appeared to match major groupings currently recognized in the taxonomy but no support was evident for nearly all the higher level groupings. Nevertheless, some interesting insights were gained in relation to the phylogenetic relationships among some genera under study. Meanwhile, the phylogenetic relationship among Mahseer fishes (genus Tor and Neolissochilus) were poorly resolved using the current data alone, but the taxonomic revision of other genera particularly for the genus Puntius could improve this. The current study suggest that P. binotatus and P. sealei could be representative of the genus Puntius, while any other species identified as belonging to the genus Puntius should cluster with this group. The study also revealed that two morphologically similar Barbonymus species (namely, B. gonionotus and B. schwanenfeldii) were phylogenetically distinct (13.0% K2P genetic distance). This indicated that a taxonomic revision of B. gonionotus would be required from its current position within the genus Barbonymus. The results of the current study also revealed two interesting findings for Hampala; (1) the Borneo endemic Hampala forms are distinct from the widespread H. macrolepidota, and (2) two distinct lineage were evident in H. bimaculata from Sarawak. In general, the sequence analysis of the cytochrome b mtDNA region has been proven to be useful for assessing phylogenetic relationships among indigenous freshwater fishes in Malaysia.